Nutlet and leaf micromorphology in some Turkish species of Teucrium L. (Lamiaceae) - Ecevit-Genç, Gülay; Özcan, Taner; Dirmenci, Tuncay (Phytotaxa, 2017)
Nutlet and leaves micromorphology of 27 Teucrium taxa were examined using SEM. The significant variation was found on the nutlet surface ornamentation and indumentum and this is mainly useful at the sectional level. Besides, trichome micromorphology is crucial to distinguish of some species inside some sections. The epidermal features of the nutlets which are specific to each section were determined. There are eglandular and glandular trichomes on the leaves and the nutlets. The glandular trichomes have two types: clavate and subsessile. The clavate glandular trichomes consist of short and long clavate. The eglandular trichomes have two types: simple unbranched and simple branched trichomes. The simple unbranched trichomes are classified as thin-walled and thick walled. The indumentum type has high taxonomical value among the species. Furthermore, leaf and nutlet micromorphological features of T. chamaedrys subsp. lydium, T. chamaedrys subsp. tauricola, T. chamaedrys subsp. sinuatum, T. divaricatum subsp. graecum, T. flavum subsp. hellenicum, T. leucophyllum have been comparatively presented for the first time. The leaf features of T. aladagense, T. chamaedrys subsp. trapezunticum and nutlet features of T. divaricatum subsp. divaricatum are also reported in detail for the first time.